An Analysis of Strategies Used in Translating the Metaphorical expressions in Harry Potter and Goblet of Fire movie - ., Ni Made Pastiyari; ., Drs.Gede Batan,MA; ., G.A.P. Suprianti, S.Pd., M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2016)
Tujuan dari penelitian ini adalah untuk mengetahui strategi yang digunakan oleh penerjemah dalam menerjemahkan ekspresi metafora yang terdapat dalam filem Harry Potter and the Goblet of Firei. Penelitian ini merupakan penelitian kualitatif dimana data tersebut dijelaskan secara deskriptif. Dalam pengumpulan data, peneliti menggunakan kuesioner dan analisis dokumen. Dalam menganalisis strategi yang digunakan oleh penerjemah dalam menerjemahkan ekspresi metaforis, peneliti menggunakan teori Larson (1984). Hasil penelitian menunjukkan bahwa ada empat strategi yang diterapkan oleh penerjemah dalam menerjemahkan metafora. Mereka Metafora diterjemahkan kedalam metaphora, (10 data), metafora diterjemahkan kedalam Simile (1 data). Metafora diterjemahkan kedalam term yang sama dengan bahasa target (1 data) and metafora diterjemahkan kedalam non-kiasan(7 data). Kata Kunci : metafora, penerjemahan, strategi penerjemahan. The aim of this study is to find the strategies used by the translator in translating the metaphorical expressions in Harry Potter and Goblet of Fire movie. This study is qualitative study in which the data were analyzed descriptively. In collecting the data, the researcher used questionnaire and document analysis. In analyzing the strategies used by the translator in translating the metaphorical expression, the researcher used Larson’s theory (1984). The result shows that there are four strategies applied by the translator in translating the metaphorical expressions. They are The Metaphor is maintained (10 data), Translating the Metaphor as Simile (1 data) 3). Substitute the Metaphor with Similar Term in Target Language (1 data), Translating the Metaphor without Keeping the Metaphorical Imagery (7 data). keyword : metaphor, translation strategies, translation.